CRISPR-Cas9-Based Technology for Studying Enteric Virus Infection - Hirano, Junki; Murakami, Kosuke; Hayashi, Tsuyoshi (Frontiers in Genome Editing, 2022)
Enteric viruses, including numerous viruses that initiate infection in enteric canal, are recognized as important agents that cause wide spectrum of illnesses in humans, depending on the virus type. They are mainly transmitted by fecal-oral route with several vector such as contaminated water or food. Infections by enteric viruses, such as noroviruses and rotaviruses, frequently cause widespread acute gastroenteritis, leading to significant health and economic burdens and therefore remain a public health concern. Like other viruses, enteric viruses ‘‘hijack’’ certain host factors (so called pro-viral factors) for replication in infected cells, while escaping the host defense system by antagonizing host anti-viral factors. Identification(s) of these factors is needed to better understand the molecular mechanisms underlying viral replication and pathogenicity, which will aid the development of efficient antiviral strategies. Recently, the advancement of genome-editing technology, especially the clustered regularly interspaced short palindromic repeat (CRISPR)-Cas9 system, has precipitated numerous breakthroughs across the field of virology, including enteric virus research. For instance, unbiased genome-wide screening employing the CRISPR-Cas9 system has successfully identified a number of previously unrecognized host factors associated with infection by clinically relevant enteric viruses. In this review, we briefly introduce the common techniques of the CRISPR-Cas9 system applied to virological studies and discuss the major findings using this system for studying enteric virus infection.